Respuesta :
Answer:
(-8)/27
Step-by-step explanation:
Simplify the following:
(-2)/(3 (2 + 1/4))
Put 2 + 1/4 over the common denominator 4. 2 + 1/4 = (4×2)/4 + 1/4:
(-2)/(3 (4×2)/4 + 1/4)
4×2 = 8:
(-2)/(3 (8/4 + 1/4))
8/4 + 1/4 = (8 + 1)/4:
(-2)/(3 (8 + 1)/4)
8 + 1 = 9:
((-2)/3)/(9/4)
Multiply the numerator by the reciprocal of the denominator, ((-2)/3)/(9/4) = (-2)/3×4/9:
(-2×4)/(3×9)
3×9 = 27:
(-2×4)/27
-2×4 = -8:
Answer: (-8)/27
Answer:
-8/27
Step-by-step explanation:
-2/3 ÷ 2 1/4
Change to an improper fraction
-2/3 ÷ ( 4*2+1)/4
-2/3 ÷9/4
Copy dot flip
-2/3 * 4/9
-8/27